2007
DOI: 10.4037/ajcc2007.16.6.544
|View full text |Cite
|
Sign up to set email alerts
|

Capnometry and Air Insufflation for Assessing Initial Placement of Gastric Tubes

Abstract: Background Nurses are often responsible for placement of large-bore gastric tubes. Tube misplacement into the lungs is a potential complication with serious sequelae. The reliability of common bedside methods for differentiating between pulmonary and gastric placement has not been acceptable. Objective To compare the accuracy of capnometry (colorimetric indicator of end-tidal carbon dioxide) and air insufflation/auscultation with the accuracy of radiography in detecting the location of gastric t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Some techniques to reduce the risk for pulmonary placement include listening for air exchange at the end of the tube after 25 cm tube length has been inserted, 22 carbon dioxide calorimetry, [33][34][35][36] and tube placement check by radiograph. 37 Fluoroscopic and endoscopic guidance for feeding tube placement have been utilized, and placement is verified during tube placement.…”
Section: Nasally Placed Feeding Tubes: Placementmentioning
confidence: 99%
“…Some techniques to reduce the risk for pulmonary placement include listening for air exchange at the end of the tube after 25 cm tube length has been inserted, 22 carbon dioxide calorimetry, [33][34][35][36] and tube placement check by radiograph. 37 Fluoroscopic and endoscopic guidance for feeding tube placement have been utilized, and placement is verified during tube placement.…”
Section: Nasally Placed Feeding Tubes: Placementmentioning
confidence: 99%
“…However, these tests can result in false positive results in 16% of cases when compared with X-rays. 18 They are also unable to positively confirm misplacement of the NGT in the mouth, nasopharynx or oesophagus. 19 …”
Section: Introductionmentioning
confidence: 98%
“…Measuring pH of gastric aspirate is another reliable indicator for tube placement. However, studies have confirmed that radiography is superior to other technique despite the risk of radiation exposure, but if not available, pH method can be applied (10,38,(46)(47)(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%